A study on elevation of troponin I in ischemic stroke as an independent prognostic marker of outcomes - Thapa, Pradeep; Agrawal, Jagdish Prasad; Baniya, Rajani (Nepal Journal of Neuroscience, 2020)
Background: Stroke is the second leading cause of death worldwide, comprising approximately 10% of all deaths. A substantial number of stroke patients have elevated cardiac troponin levels and are associated with poorer prognosis. Methods: This was a prospective observational study conducted for 1 year at Tribhuvan University Teaching Hospital, in which 101 acute ischemic stroke patients were enrolled. Data included vital signs, laboratory parameters, and clinical features evaluated at the time of admission. The National Institute of Health Stroke Scale (NIHSS) and modified Rankin scale (mRS) were used to assess stroke severity and outcomes. Results: Elevated troponin I (> 0.034 ng/mL) was observed in eight (7.9%) patients. Compared to patients with normal troponin I, patients with elevated troponin I were older(mean age 61vs 59.68 years), had higher blood glucose( 10.6 vs. 7.04 mmol/L), higher median white blood cells( 9.3 vs. 8.9 1,000/m3) and creatinine levels(119.5 μmol/L vs. 95.9 μmol/L), higher mean NIHSS scores on admission(16 vs. 8.6), and discharge(14.5 vs. 6.8), higher median mRS scores( 4.13 vs. 1.8) at discharge(p<0.001). Poor outcomes were observed in 34(33.66%) patients of 101 patients and death occurred in five (4.9%) patients. Patients with abnormal troponin I had poorer outcomes than normal troponin I level patients (p=<0.001) and significantly higher deaths (p=0.006). Univariate analysis of continuous variables revealed that patients with poor outcomes compared to good outcomes had higher troponin levels (0.029 vs. 0.013 ng/mL, p=0.001), creatinine levels (113.5 vs. 89.8μmol/L, p=0.007), NIHSS score on admission (13.4 vs. 5.10, p<0.001),discharge (12.4 vs. 5.1, p<0.001), and higher mRS scores at discharge (3.71 vs. 1.16, p<0.001).Multiple logistic regression analysis revealed that NIHSS score on admission>13(OR 15.902; 95%CI[3.65-69.28],p=<0.001) and abnormal troponin I level, troponin I>0.029 ng/mL (odds ratio[OR]:28.451; 95% CI[2.785-290.6],p=0.005) were significant predictors of poor outcomes. Significant predictor of in hospital mortality only included troponin I level >0.04 ng/mL (0R 0.071; 95% CI [0.005-1.037], P=0.05). Conclusion: Troponin I provide better information than age and other laboratory parameters in the prediction of outcomes of stroke. Elevation of troponin I during acute stroke is a strong predictor of both poor outcomes and in-hospital mortality.